2019
DOI: 10.1111/php.13106
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Bioluminescence of the Humboldt Squid, Dosidicus gigas (d'Orbigny, 1835): One of the Largest Luminescent Animals in the World

Abstract: Bioluminescence is found in a number of cephalopods, such as Watasenia scintillans and Sthenoteuthis oualaniensis; however, many species remain poorly studied, including the Humboldt squid, Dosidicus gigas. This is the largest member of the Ommastrephidae family and grows to 2 m in length, making it one of the largest luminescent animals ever observed. Humboldt squid have small photophores all over their body that emit a brilliant blue luminescence. Using lyophilized photophores from squid caught off the coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Secreted bioluminescence, which is used for mating and defence, is discharged from light organs such as modified mouths, photophores, and appendages (Angel, 1968; Nicol, 1969; Barnes & Case, 1972; Abe et al ., 2000; Robison et al ., 2003; Wong et al ., 2015). Alternatively, internal extracellular and intracellular bioluminescence, which is used for counterillumination, prey capture, mating, and communication, is produced in light spots associated with the epithelium, light organs connected to the digestive tract, luminous lanterns, or structurally complex photophores (Peterson & Buck, 1968; Arnold & Young, 1974; Baguet, 1975; Haddock & Case, 1999; Thacker & Roje, 2009; Galeazzo et al ., 2019).…”
Section: Bioluminescence: An Excellent System For Studying Convergencmentioning
confidence: 99%
See 2 more Smart Citations
“…Secreted bioluminescence, which is used for mating and defence, is discharged from light organs such as modified mouths, photophores, and appendages (Angel, 1968; Nicol, 1969; Barnes & Case, 1972; Abe et al ., 2000; Robison et al ., 2003; Wong et al ., 2015). Alternatively, internal extracellular and intracellular bioluminescence, which is used for counterillumination, prey capture, mating, and communication, is produced in light spots associated with the epithelium, light organs connected to the digestive tract, luminous lanterns, or structurally complex photophores (Peterson & Buck, 1968; Arnold & Young, 1974; Baguet, 1975; Haddock & Case, 1999; Thacker & Roje, 2009; Galeazzo et al ., 2019).…”
Section: Bioluminescence: An Excellent System For Studying Convergencmentioning
confidence: 99%
“…Photoproteins using coelenterazine as a substrate can also vary in terms of the cofactors required to produce bioluminescence. For example, cnidarians, ctenophores, and radiolarians use the divalent cation Ca 2+ as a photoprotein cofactor, but the squids Dosidicus gigas and Sthenoteuthis oualaniensis use a monovalent cation cofactor such as Na + or K + (Shimomura, 1985; Takahashi & Isobe, 1994; Tsuji et al ., 1995; Galeazzo et al ., 2019). This biochemical variability in bioluminescence reveals that there are numerous biological approaches to harnessing coelenterazine‐based bioluminescence.…”
Section: Reviewing the Multi‐level Convergent Evolution Of Bioluminesmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors suggested that symplectins may have multiple functions including hydrolase activity (Francis et al, 2017). Both dehydrocoelenterazine and symplectin-like photoprotein were recently demonstrated to be responsible for the light emission of the Humboldt squid, Dosidicus gigas, one of the largest cephalopods on Earth (Francis et al, 2017;Galeazzo et al, 2019).…”
Section: Sthenoteuthis-type Photoproteins or Symplectin (Group Vii)mentioning
confidence: 99%
“…Numerous (a single D. gigas may have hundreds) small subcutaneous (s.c.) photophores that consist of relatively rudimentary aggregations of photogenic tissue are embedded throughout the muscle tissue ( Fig. 3 A-C) and cause the entire animal to glow (45)(46)(47)(48)(49). Pigmentation patterns are generated by the overlying chromatophore layer, which is cutaneous.…”
Section: Bioluminescent Backlighting and The Illumination Of Chromaticmentioning
confidence: 99%